HUBUNGAN ANTARA NYERI MUSCULOSKELETAL DISORDERS DENGAN KUALITAS TIDUR PADA TENAGA KEPERAWATAN RUMAH SAKIT X - Al Fatih Lois Ariansyah (2023)
Background: There are 2 million cases of musculoskeletal disorders every year. In Indonesia, health problems indicate that around 40.55% of diseases are experienced by workers who have something to do with work, including musculoskeletal Disorders (MSDs) as much as 16%. Nursing staff can experience musculoskeletal disorders such as shoulder pain, low back pain which is something that is often encountered every day and has the highest prevalence worldwide. When experiencing musculoskeletal disorders, pain, soreness and discomfort can occur in certain positions. Research objective: To determine the relationship between pain in musculoskeletal disorders and sleep quality of nursing staff. Research method: This study used a cross-sectional method. With a sample of 60 nursing staff, this research was carried out using a questionnaire with the Nordic Body Map and PSQI (Pittsburgh Sleep Quality Index) measurement tools.